Outside-In Subepicardial Dissection During Percutaneous Epicardial Ventricular Tachycardia Ablation. (October 2016) - Jincun, Guo; Faguang, Zhou; Weibin, Huang; Yan, Wang; Kang, Dong; Tung, Roderick
Abstract : Supplemental Digital Content is available in the text.